PEMODELAN SPEKTRUM SERAP DAN PANCAR ROTASI MOLEKUL UNTUK MENENTUKAN MOMEN INERSIA DAN MOMENTUM SUDUT ORBITAL - S, Ego Srivajawaty; Ngaderman, Hubertus (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2016)
[Theory, computation and modeling] The purposes of this research are modeling rotation of the molecule, emiting or absorption energy. The parameters which involved for the rotation spectrum are molecular mass, inertia moment, quantum numbers and angular momentum orbital. Made a pitch for a molecular spectrum rotation and inertia moment will be used methods from concept classical mechanics. Quantum mechanical used for determining angular momentum orbital. The spectral energy was counted for a molecular rotation and i.e and . Specific electromagnetics radiation for the energy absorption spectrum and emiting diatomic molecular at the moment that molecular vibrating were in the region spectrum infrared, whereas if the molecular rotated then its on the far infrared and microwave region. Transition which emited measured up by selection rules that only commit for the quantum numbers change as many as one unit, where identics with as the quantum number for one atomic hidrogen. was a quantum number take the values .Transition which emited doesnât have all the same energy, but rather form a series energy which descend (or a series which go up wave length).